Nonlinear and adaptive control systems - Ding, Zhengtao (The Institution of Engineering and Technology, 2013)
The book reviews developments in the following fields: nonlinear systems; adaptive systems; state space models; describing functions; advanced stability theory; feedback linearisation; adaptive control of linear systems; nonlinear observer design; backstepping design; disturbance rejection; output regulation; and control applications.